Uso compasional de tigeciclina intraventricular en pacientes con ventriculitis causada por Enterococcus faecium. Reporte de seis casos pediátricos - Gloria Celeste Samudio-Domínguez (Asociación Colombiana de Infectología, 2020)
Introduction: Tigecycline is a drug of restricted use in pediatrics. The use of this antibiotic intraventricularly is a decision of compassive use in cases of highly resistant bacteria, and in cases where there is no other alternative. Clinical case: We present six cases of patients with a diagnosis of ventriculitis caused by Enterococcus faecium, who received intraventricular tigecycline with successful microbiological evolution. The doses used intravenously and intraventricularly are discussed. Conclusions: the use of this antibiotic intraventricularly can be a successful alternative in cases of highly resistant germs, when there are not alternative options.